All Culture is Local Good Practice in Regional Cultural Mapping and Planning from Local Government - Andersen, Lisa; Malone, Margaret (UTS ePRESS, 2013)
This book is an outcome from a five year Australian Research Council funded research project, CAMRA cultural asset mapping in regional Australia project (LP0882238). Over this time four universities, four local governments, and peak regional, state and federal agencies sought to develop knowledge that would enable better informed planning for arts and cultural development in rural and regional communities. Over the course of the project, it became evident that rural-regional local government staff and cultural decision makers need better place-specific data and are keen to learn from the experiences of other local governments to inform their own planning. This book is CAMRA's response to that need and includes 17 case studies on good practice in (1) Cultural Mapping and Data Collection and (2) Cultural Planning. The case studies have been written with the aim of making ideas and processes transferrable for any regional local authority - with the resource implications made clear - and are ordered using Australian Standard Geographical Classification-Remoteness Areas for local government area.